IMPLEMENTATION OF BAI ‘BITSAMAN AJIL (BAA) FINANCING TO INCREASING INCOME ON BMT AT-TAQWA MUHAMMADIYAH BANDAR BUAT BRANCH - Fitri Yenti; Siska Febrianti; Dola Olivia Veranti (Jurnal Apresiasi Ekonomi, 2019)
The purpose of this study is to describe the procedure for the implementation of Bai ’Bitsaman Ajil (BBA) financing at BMT Taqwa Muhammadiyah Branch Bandar Buat. The data source of this study was obtained from the manager of BMT Taqwa Muhammadiyah Bandar Bandar branch. Based on the results of the research conducted by the author, that BMT At-Taqwa Muhammadiyah Bandar Buat Branch has established a financing procedure that must be met by each prospective customer starting with the customer submitting a request for financing, the Account Officer (AO) conducts a survey to the place of business and residence, Account Officer (AO) calculates customer cash flaw (cash flow), realization of financing proposals, and the latter pays installments to BMT